The central nervous system depressant activities of Mycotoxin MT81 and its Acetylated and Benzoylated analogues - Sujata Maiti Choudhury (Al Ameen Medical College, 2008)
Mycotoxin MT81 isolated from Penicillium nigricans and its two structural derivatives viz. Acetylated MT81 (AcMT81) and Benzoylated MT81 (BzMT81) show antimicrobial activities as well as cause hepatotoxicity and nephrotoxicity. Present study deals with the CNS depressant activity of the above said toxins. Sedative-hypnotic and hypothermic actions were assessed by injecting MT81, AcMT81, and BzMT81 at three different doses prior to the administration of diazepam, chloropromazine and pentobarbitone respectively. The analgesic actions were studied by hot plate method. The sleep induced by diazepam, chlorpromazine and pentobarbitone were prolonged following the administration of MT81, AcMT81 and BzMT81. Significant hypothermia produced in a dose-dependent manner after the treatment with MT81 and its two derivatives. The toxins also potentiated the analgesic action of morphine significantly (p≤0.001). Being less toxic than the parent toxin MT81, the structural analogues showed more prominent analgesic activities, sedative effects and hypothermic actions.